LEGAL ASPECTS MISUSE OF ISSUER MATERIAL INFORMATION BY NOTARIES FOR PERSONAL INTEREST - Siregar, Mahmul; Sukarja, Detania; Keizerina Devi Azwar, T; Rizki Putra, Rahmat (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2022)
Notaries are one of the professions that are very close to crime in the capital market, because notaries have an important role for issuers so that notaries have inside information. Notaries are very vulnerable to inside trading crimes. This research uses normative legal research methods and empirical legal research. Therefore, the data used include primary data and secondary data. Data were collected using library research and field research using interview methods. Furthermore, the data were analyzed using qualitative data analysis methods. Notaries can be held accountable if the notary is proven to have misused material information, where the examination is carried out by the OJK as the party that oversees the capital market. Responsibilities that can be requested by a notary include criminal liability, namely a 10-year prison sentence and a fine of 15 billion rupiah and civil which can be prosecuted under Article 1365 of unlawful acts, besides that there are also administrative responsibilities and code of ethics responsibilities.